Embodiment, enaction, and the lived body in foreign language learning: a novel conception of action-oriented language education - Witte, Arnd (Frontiers in Language Sciences, 2026)
In educational settings, theory and practice of foreign language (FL) learning have been dominated by a cognitive output-driven notion of an ostensibly quantifiable “efficiency” of FL learning. The concepts of enaction and embodiment challenge the conventional view of language learning by positing that the learner's organism endows components of the environment with specific meaningfulness, and the environment provides the organism with specific affordances, activating modality-specific brain areas. Hence, cognitive learning processes can no longer be understood as linear input-output functions for accumulating information in the brain but must involve the sensory and motor capacities of learners' bodies. Action-oriented foreign language learning scenarios mobilize preverbal (inter)corporeal experiences, which are actually lived through in multisensorial and multimodal experiences. Whereas methodologies promoting bodily activation emphasize learners becoming more attuned to the foreign language-framed eco-social environment and its semiotic resources, they tend to overlook the aspect of the learner's immaterial lived body and its pre-reflective resonances with and responses to actually experiencing the FL and its manifestations which is vital for connecting subjective corporeal memories to the FL learning process. What was corporeally sensed as striking resonances can be made explicit through attentiveness and reflective verbal explication. Conversely, learned items appear to be more meaningful to the learner when the situated affective background shines through. Since language is a form of embodied sociality, the objective for FL learners is to incorporate the foreign language as an integrated semiotic repertoire for sociocultural behavior through body mobilization and enhanced attentiveness to the preverbal resonances and responses of their lived body.